Gustavo, the shy ghost ebook - Drago, Flavia Z. (The World of Gustavo, 2020)
This winning debut picture book from Mexican artist Flavia Z. Drago about finding the courage to make friends is perfect for the spooky season — or anytime. Gustavo is good at doing all sorts of ghostly things: walking through walls, making objects fly, and glowing in the dark. And he loves almost nothing more than playing beautiful music on his violin. But Gustavo is shy, and some things are harder for him to do, like getting in a line to buy eye scream or making friends with other monsters. Whenever he tries getting close to them, he realizes they just can't see him. Now that the Day of the Dead is fast approaching, what can he do to make them notice him and to share with them something he loves? With fancifully detailed artwork and visual humor, debut picture-book creator Flavia Z. Drago's vivid illustrations tell a sweet and gently offbeat story of loneliness, bravery, and friendship that is sure to be a treat for little ghouls and goblins everywhere.